Proceedings of the 5th EAI International Conference on Wireless Mobile Communication and Healthcare - "Transforming Healthcare 2015
DOI: 10.4108/eai.14-10-2015.2261638
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Deployment Challenges of Health Monitoring Devices for a Dementia Study

Abstract: This paper presents the findings of a technological adoption assessment of health monitoring devices for a dementia study. The work was motivated by the need to monitor physical activity interventions in a study cohort of dementia patients living with caregiver support in the community. The system requirements were for a discrete and unobtrusive solution with activity level (energy expenditure) and heart rate monitoring. In addition to fulfilling system requirements, successful technology adoption requires car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The selection of an appropriate activity monitor for a given study is typically determined by the required parameter acquisitions and deployment needs [24] as well as the study budget. However, the calibration and validation of devices [25,26] can be onerous.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of an appropriate activity monitor for a given study is typically determined by the required parameter acquisitions and deployment needs [24] as well as the study budget. However, the calibration and validation of devices [25,26] can be onerous.…”
Section: Introductionmentioning
confidence: 99%
“…Due to issues of cognitive limitations and other risk factors associated with aging, studies have suggested that elderly users, especially PWDs exhibit resistance to the use of healthcare devices [ 2 , 13 ]. Notwithstanding the existence of these studies, other research and projects have demonstrated that, with the right approach to design considerations, this resistance could be reduced tremendously, leading to the adoption of wearable devices by PWDs [ 14 , 15 , 16 , 17 , 18 , 19 ]. For instance, studies have revealed that GPS-based wireless tracking devices, such as GPS Smart Sole, Freedom GPS Locator Watch, Safe-link, Mindme Locate, MXLOCareTM, iTraq3, and PocketFinder+, and others, such as Fitbit, Mi band, Oura ring, and Alice PDx, have been preferred and widely used by PWDs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%